Social Networking as a Marketing Tool: Study of Consumers’ Attitudes toward Brands Using Facebook to promote their Marketing Activities in Thailand - Arpanantakul, Manita (2013)
Social media has become an essential part of modern life as it intensely transforms the way people interact and transact with each other. With the increasing popularity on social media usage, Facebook has become one of the most popular and widely used in Thailand, making it an ideal place for marketing promotion activities.